Protection mechanisms against excess light in Myrothamnus flabellifolius (Welw.) - Bartsch, Silke (Department of Biological Sciences, 2023)
The effects of light stress during drying on excised twigs of the homoiochlorophyllous resurrection plant Myrothamnus flabellifoius, was examined in this study. Leaves were prevented from folding during drying and plants were dried in the light, and as a control, in the dark. The effects on the photoprotection mechanisms were assessed. Differences in water content, quantum efficiency of photosystem II. chlorophyll (a+b) content, carotenoid content. anthocyanin contents were measured during dehydration and rehydration. Ultrastructural studies and examination of electrolyte leakage provided an indication of the subcellular changes in leaf tissues. There was no significant difference in the protectron mechanisms of restrained and unrestrained leaves during dehydration and rehydration. Thus. it seems that leaf folding is not a critical faclor in terms of achieving desiccation tolerance in M. flabellifolius. because both treatments were able to survive drying. Leaves that were dried in the dark showed extensive subcellular damage during dehydration and quantum efficiency of photosystem II did not recover fully on rehydration. It is suggested that some of the protectlon mechanisms against desiccation-induced dama.9e cannot be activated or sufficiently upregulated 1n the absence of fight.